Boric acid treated HZSM-5 for improved catalyst activity in non-oxidative methane dehydroaromatization. Issue 12 (3rd April 2020) - Balyan, Sonit; Haider, M. Ali; Khan, Tuhin S.; Pant, K. K.
Abstract : The dehydroaromatization (DHA) reaction of methane under non-oxidative conditions is carried out over a molybdenum catalyst supported on HZSM-5 and boric acid (BA) treated HZSM-5 at 700 °C and atmospheric pressure. Abstract : The dehydroaromatization (DHA) reaction of methane under non-oxidative conditions is carried out over a molybdenum catalyst supported on HZSM-5 and boric acid (BA) treated HZSM-5 at 700 °C and atmospheric pressure. As compared to the conventional Mo/HZSM-5 catalyst, wherein a maximum of 100 nmol gcat −1 s −1 of benzene is measured, BA treated Mo/HZSM-5 exhibited a significantly high benzene formation rate (∼420 nmol gcat −1 s −1 ) at around 90 minutes time on stream. In addition, a boron treated catalyst was measured to have an 8 wt% reduction in coke formation as compared to the untreated catalyst. One prevailing thought for improved activity is ascribed to the desired moderation of Brønsted acid sites on BA treatment. This is probed by temperature programmed desorption (TPD) experiments which indicated an overall reduction in Brønsted acidity on BA treatment of the catalyst. Quantum mechanical density functional theory (DFT) calculations further estimated a high deprotonation energy (DPE) of the Brønsted acidic proton anchored on the boron substituted site (DPE = 1145.4 kJ mol −1 ) as compared to the Al site (DPE = 1100.6 kJ mol −1 ) of the zeolite framework, suggesting a reduction in Brønsted acidity. FTIR and 11 B MAS NMR spectra confirmed the presence of trigonal boron species substituted in the zeolite framework. In addition, the molybdenum oxide (Mo 6+ ) species, which is known to act as the precursor for active sites in methane DHA, is observed to form in a relatively greater quantity on the boron treated catalyst in the temperature program reduction (TPR) study of the calcined catalysts. Thus, BA treatment moderates the acidity of the Mo/HZSM-5 catalyst to provide the desired active sites for high reactivity.